Development of microsatellite loci from a reference genome for the Neotropical butterfly Heliconius numata and its close relatives. Issue 2 (23rd January 2015) - Chouteau, Mathieu; Whibley, Annabel; Angers, Bernard; Joron, Mathieu
Abstract The Neotropical butterfly Heliconius numata (Lepidoptera: Nymphalidae: Heliconiinae) is known for its striking diversity of wing color patterns driven by the Müllerian mimicry of multiple local models and controlled by a single supergene locus. Such fine‐scale variation of traits under strong selection offers a unique opportunity for the study of the ecology and genetics of adaptation. However, little is still known of the population processes driving geographical variation in wing‐pattern phenotypes. We report the characterization of 26 microsatellite markers for the butterfly H. numata, including six located inside the wing color‐pattern supergene region. All markers are polymorphic, with allele numbers ranging from 2 to 21 per locus, an observed heterozygosity of 0.111 to 0.848 and an expected heterozygosity of 0.126 to 0.942. A subset of 18 of these markers was tested on five closely related sympatric Heliconius species with an amplification success ranging from 88% to 94%. The obtained set of microsatellite markers provides a new and useful set of tools to investigate patterns of differentiation and selection in populations of mimetic Heliconius butterflies. Moreover, markers developed within the color‐pattern supergene will facilitate characterization of the association between the genetic architecture and the functional diversity of wing patterns. Finally, the cross‐species amplification success of the described markers extends their utility to also encompass comparative population genetic studies of closely related species within a clade of rapidly diversifying species.